PELATIHAN PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM PENGAJARAN BAHASA INGGRIS UNTUK MAHASISWA TADRIS BAHASA INGGRIS IAIN KEDIRI - Ummy Khoirunisya’ Masyhudianti; Muhamad Safa’udin; Annisa Ayu Lestari; Edi Rozal (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service program aimed to enhance digital literacy and pedagogical competence of English Education students at IAIN Kediri through practical training on Artificial Intelligence (AI) tools in language teaching. Addressing challenges in conventional English learning and low digital integration, the program introduced AI applications such as ChatGPT, Grammarly, and Elsa Speak to improve students’ writing, speaking, and self-reflection skills. The participatory, experiential, and project-based learning approach fostered active student engagement, collaborative learning, and ethical awareness in AI use. Results showed significant improvement in students’ digital skills, pedagogical readiness, and reflective learning, alongside the emergence of a technology-savvy learning community. The program contributes to bridging the digital competence gap, preparing future English teachers for the demands of the 21st century education, and supports Indonesia’s educational transformation in the Industry 4.0 era. Keywords: Artificial Intelligence, English Language Teaching, Pedagogical Competence, Technology Integration